Manual of Cardio-oncology : Cardiovascular Care in the Cancer Patient - Lestuzzi, Chiara; Oliva, Stefano; Ferraù, Francesco (Springer International Publishing : Imprint: Springer, 2017)
This concise and handy manual provides straightforward, up-to-date guidance for cardiologists and other practitioners on the management of cancer patients with cardiac problems, whether they be due to the cancer itself or to antineoplastic treatment. Detailed attention is devoted to the various forms of cardiotoxicity associated with chemotherapy and radiotherapy. The drugs commonly responsible for each toxicity are identified and clear advice is offered on monitoring techniques and treatment approaches. In addition, the issue of cardiotoxicity due to cancer treatment in particular patient groups - children, the elderly, and those with pre-existing cardiac disease - is addressed separately, with guidance on when and how antineoplastic (and/or cardiological) treatments should be modified. Further sections describe the correct responses to cardiac problems secondary to the cancer itself, including thromboembolic disorders and electrolyte imbalances, and the diagnosis, treatment, and follow-up of cardiac tumors. A closing section considers how to improve cooperation between oncologists, cardiologists, and general practitioners to ensure that cancer patients' cardiovascular needs are met in a multidisciplinary approach.
Keywords: Medicine.; General practice (Medicine).; Cardiology.; Geriatrics.; Oncology.; Pain medicine.; Pharmacotherapy.; elektronické knihy; electronic books